A journey of two Psalms: the theory and practice of reception history through Psalms 1 and 2 - Gillingham, S (Society of Biblical Literature, 2016)
This paper will offer some further reflections (and opportunity for discussion) of my recent book, A Journey of Two Psalms: The Reception of Psalms 1 and 2 in Jewish and Christian Tradition (Oxford: Oxford University Press, 2013) in the light of a further publication Psalms through the Centuries Volume Two, which will be published by Wiley-Blackwell some time in 2017. The latter is a reception-history commentary of the entire Psalter, psalm by psalm. In the first half of the SBL paper I shall consider the methodological challenges in writing about reception history of biblical texts, and in the second half, I shall consider some of the fruits of these labours with reference to the Psalms.